Administration of secretoneurin is protective in hypoxic–ischemic neonatal brain injury predominantly in the hypoxic-only hemisphere. (3rd June 2017) - Posod, Anna; Wechselberger, Karina; Stanika, Ruslan Iljitsch; Obermair, Gerald J.; Wegleiter, Karina; Huber, Eva; Urbanek, Martina; Kiechl-Kohlendorfer, Ursula; Griesmaier, Elke
Highlights: Secretoneurin plasma levels decrease 48 h after experimental hypoxic–ischemic brain injury. Administration of secretoneurin prior to the decline attenuates brain injury in newborn mice. Injury mitigation is associated with a reduction in apoptotic cell death predominantly in the hypoxic-only hemisphere. Graphical abstract: Abstract: Neonatal brain injury is a problem of global importance. To date, no causal therapies are available. A substance with considerable therapeutic potential is the endogenous neuropeptide secretoneurin (SN), which has proven to be beneficial in adult stroke. The aim of this study was to assess its effect in neonatal hypoxic–ischemic brain injury models. In vitro, primary hippocampal neurons were pre-treated with vehicle, 1 µg/ml, 10 µg/ml, or 50 µg/ml SN and subjected to oxygen–glucose deprivation (OGD) for six hours. Cell death was assessed after a 24-h recovery period. In vivo, seven day-old CD-1 mice underwent unilateral common carotid artery ligation and were exposed to 8% oxygen/nitrogen for 20 min. SN plasma concentrations were serially determined by ELISA after insult. One hour after hypoxia, a subgroup of animals was treated with vehicle or SN. SN plasma concentrations significantly decreased 48 h after insult. The number of caspase-3-positive cells was significantly lower in the hypoxic–ischemic hemisphere in the thalamus of SN-treated animals. In the hypoxic-only hemisphere administration of SN significantly reduced the number of caspase-3-positive cells (in cortex, white matter, hippocampus, thalamus and striatum) and inhibited microglial cell activation in the thalamus. SN has neuroprotective potential in neonatal brain injury. Its main action seems to be inhibition of apoptosis in the aftermath of the insult, predominantly in the hypoxic-only hemisphere. This might be explained by the less pronounced injury in this hemisphere, where blood flow and thus nutrient supply are maintained.